Same As Ever : Timeless Lesson on Risk, Opportunity , and Living a Good Life - Housel, Morgan (Hampire : Harriman House, 2023)
"
Timeless lessons about the things that stay the same in a world that never stops changing"-- Every investment plan under the sun is, at best, an informed speculation of what may happen in the future, based on a systematic extrapolation from the known past. "Same as Ever" reverses the process, inviting us to identify the many things that never, ever change. With his usual elan, Morgan Housel presents a master class on optimizing risk, seizing opportunity, and living your best life. Through a sequence of engaging stories and pithy examples, he shows how we can use our newfound grasp of the unchanging to see around corners, not by squinting harder through the uncertain landscape of the future, but by looking backwards, being more broad-sighted, and focusing instead on what is permanently true. By doing so, we may better anticipate the big stuff, and achieve the greatest success, not merely financial comforts, but most importantly, a life well lived.
Keywords: Psychology; Developmental and Differential Psychology